ПСИХОЛОГО-ПЕДАГОГИЧЕСКИЕ ОСОБЕННОСТИ ОРГАНИЗАЦИИ УЧЕБНОЙ ДЕЯТЕЛЬНОСТИ С ДЕТЬМИ ПОДРОСТКОВОГО ВОЗРАСТА - Кенжебаева, К. (SCIENCE and SOCIETY, 2024)
The article discusses the social activity of adolescence, which is generally focused on the assimilation of values characteristic of the adult world, as well as the main features of this period, i.e. accelerated process of child development, formation of self-awareness, desire for independence, activity, self-affirmation.